Severe digestive hemorrhages in spleen hydratic cyst - Valls, Alberto (Cirugía del Uruguay, 2020)
Digestive hemorrhages are discussed as an unusual complication of the hydatid cyst in the spleen, the knowledge whereof is of importance in its surgical solution. Hemorrhages are explained by 3 mechanisms: 1) the most important one, is by compression of the spleen vein by retro or subpedicle cysts which leave gastrosplenic anatomosis free; 2) by hypersplenism; 3) by perforation of the cyst in the stomach.